Nonprescription medication purchases and the role of pharmacists as healthcare workers in self-medication in Istanbul - (:unkn) unknown (INT SCIENTIFIC INFORMATION, INC, 2007)
In Turkey, some drugs call be purchased from pharmacists without a prescription and there is no legal classification corresponding to the international term over-the-counter drugs. The purpose of this study was to identify these non-prescribed drugs and to define the role of pharmacists in their sale and their use in primary healthcare. This cross-sectional study was carried out in Istanbul between December 1, 2003, and August 31, 2004. Seventy-three of the 901 pharmacies in two districts of Istanbul were chosen with systematic sampling, and information concerning drug sales and pharmacists' behavior regarding primary healthcare services was collected by observations as well as by interviews with the pharmacists. The study demonstrated that 41% of the drugs sold were non-prescribed. In pharmacies remote front healthcare institutions, remote from district centers, and in the summer seasons, the rates of non-prescribed drug sales were higher than those of prescribed (chi(2)=10.5, d.f.=10.5, d.f.=1, p=0.001; chi(2)=62.8, d.f.=1, p=0.0001; chi(2)=23.4, d.f.=1, p=0.0001). The pharmacists stated that aside from drug sales, consumers visited them to consult about drugs, to get information oil their health status, and to learn about, family planning (78.1%, 72.1%, and 72.6% of the pharmacists, respectively). Extensive sale of non-prescribed drugs as a response to public demand, including diose used for serious illnesses, has been observed in private pharmacies in Istanbul. The role of pharmacies and pharmacists in primary healthcare should be discussed more thoroughly and redefined oil a legal basis.
Keywords: pharmacists; self-medication; over-the-counter drugs; healthcare workers; non-prescription drugs; Istanbul-Turkey; PREVALENCE; PRESCRIPTION; DRUGS